The Study of Best Slope Protection Method due to Slope Failure at Section 6 for East Cost Rail Link (ECRL) - IRSYAD AZMI, MUHAMMAD IRSYAD; MUSLI NIZAM, MUSLI NIZAM BIN YAHYA; Azmin Ariff Abdul Azij, (Progress in Engineering Application and Technology, 2024)
Slope protection is a critical aspect of land and landform management, especially in steep areas that can cause collapse and endanger lives and infrastructure. Normally, slope protection used is close turfing and hydroseeding due to its cost effective and less construction time. However, the occurrence of slope erosion in the ECRL project where it involves the failure of the hydroseeding method as slope protection. Therefore, this study focuses on the settlement behavior comparison between the herringbone and hydroseeding methods as slope protection by utilizing instrumentation and monitoring on the slope. The method used in this study is to study better slope stability in line with their purpose as slope protection methods within CH408-CH409 in the ECRL projects. Inclinometer has been chosen as instrument to conduct a monitoring on slope displacement on CH408 until CH409. The monitoring period began with the occurrence of slope failure and continued until the implementation of a new slope protection method, the herringbone technique. The results of this study demonstrate that the herringbone method outperforms the hydroseeding method for slope protection. This conclusion is based on observations of settlement behavior and slope stability, as determined by the soil investigation conducted in the study area. The rate of slope displacement for both hydroseeding and herringbone methods was recorded to compare their stability as slope protection techniques. The findings of this study will contribute to the construction industry, particularly in railway projects, where it can be applied to the construction of subgrades involving cutting and filling embankments.